Strengthening Civic Disposition, Sport Character, and Ethical Digital Communication through Deep Learning–Based Digital Projects - Wulandari; Syahrul Darwis; Rosdiawati; Maryam; Nurwafiqah Amirah Budi; Elihami; Misran (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to analyze the effectiveness of a Deep Learning-based digital project in strengthening Civic Disposition, sports character, and ethical digital communication in Generation Z students at SMPN 4 Anggeraja. The study used a one-group pretest-posttest design involving 64 seventh and eighth grade students. Data were collected through questionnaires, observations, and documentation, then analyzed descriptively. The results showed an improvement in all variables after the implementation of the Deep Learning-based digital project. Civic Disposition scores increased from 63.25 to 81.47, sports character from 65.18 to 83.26, and ethical digital communication from 61.94 to 84.02. These findings indicate that the Deep Learning-based digital project is effective in developing civic attitudes, sports character, and the ability to communicate politely and responsibly in the digital space. Thus, this approach can be a relevant learning alternative to support character building and 21st-century competencies in Generation Z students.